Heterogeneous effects of international migration: evidences from Bangladesh. - Silvio Traverso (Università degli studi di Firenze, 2016)
Despite the general consensus regarding the important role played by international migration in the development of Bangladesh, little has been done to quantitatively estimate its effects. Within the framework of Rubin's causal model, this paper contributes to the literature estimating the net impact of international migration on the welfare of the members of households with migration experience. By taking advantage of the non-parametric nature of matching estimators, the effect of migration is disaggregated on the basis of expenditure quartiles and length of migration period. Additionally, the estimated counterfactual outcomes of migrant households are used to build a transition matrix showing the effect of migration on social mobility. The effect of migration turns out to be positive and statistically significant, even though its magnitude is considerably affected by technical assumptions regarding household economies of scale. International migration appears to be a risky strategy which, if successful, leads to a substantial increase of the well being of migrant households' members. Finally, moving on to normative considerations, the paper argues that the resources deployed for pro-migration policies do not directly benefit the poorer sections of the population.
Keywords: F22; O12; O15; O53; 330; International migration; Counterfactual framework; Matching estimation; Bangladesh